The Role of Youths to Promote Global City in Medan Petisah Subdistrict - Sari, Mi'raj Purnama; Revida, Erika; Rujiman (TALENTA Publisher, Universitas Sumatera Utara, 2022)
The purpose of this study to analyze the role of youth in promoting a local city with global characteristics and to find out the obstacles of promotional activities carried out by youth in Medan Petisah sub-district. The research method used descriptive qualitative and the analysis technique consists of three activities simultaneously, namely data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that the active role of youth as a moral force has been going well, but the active role of youth as social control in the research location itself has not been seen significantly and the active role of youth as agents of change from observations in the field shows that several indicators of youth as the change agent has been made but still needs to be improved. The obstacles faced by youth are The special youth portal that has been prepared cannot be used optimally, as a result youth who want to join still have to register manually and the local government is considered not to have realized the potential of youth. In addition, the facilities and infrastructure to support promotional activities are not sufficient, nor is there a budget and a special community for youth in carrying out promotional activities.